2010
DOI: 10.1182/blood-2010-03-275800
|View full text |Cite
|
Sign up to set email alerts
|

Superior outcomes associated with complete response in newly diagnosed multiple myeloma patients treated with nonintensive therapy: analysis of the phase 3 VISTA study of bortezomib plus melphalan-prednisone versus melphalan-prednisone

Abstract: , and treatment-free interval (HR ‫؍‬ 0.38, P < .0001) versus partial response, but there was no significant difference in overall survival (HR ‫؍‬ 0.87, P ‫؍‬ .54); similar differences were seen with CR versus very good partial response by uniform criteria. Quality of response improved with prolonged VMP treatment, with 28% of CRs achieved during cycles 5-9. CR duration appeared similar among patients with "early" (cycles 1-4) and "late" CRs (cycles 5-9) and among patients receiving 9 versus < 9 cycles of bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
81
2
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(100 citation statements)
references
References 37 publications
13
81
2
4
Order By: Relevance
“…[1][2][3][4][5] Three-drug combinations with bortezomib and/or thalidomide or lenalidomide appeared to be superior to most 2-drug combinations of the same agents in patients with newly diagnosed MM. The lenalidomide, bortezomib, and dexamethasone (RVD) regimen and the bortezomib, pegylated liposomal doxorubicin (PLD), and dexamethasone (VDD) regimens are among the most active in this setting, producing high rates of very good partial response (VGPR), complete response (CR), and near CR (nCR).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Three-drug combinations with bortezomib and/or thalidomide or lenalidomide appeared to be superior to most 2-drug combinations of the same agents in patients with newly diagnosed MM. The lenalidomide, bortezomib, and dexamethasone (RVD) regimen and the bortezomib, pegylated liposomal doxorubicin (PLD), and dexamethasone (VDD) regimens are among the most active in this setting, producing high rates of very good partial response (VGPR), complete response (CR), and near CR (nCR).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of a long PFS and achieving a (clinical) CR are consistent with the findings both of Tam et al (2014), who showed that patients treated with FCR with a first‐line PFS longer than 3 years survive better in the long‐term than those with PFS <3 years, and also of the VISTA (Velcade ® as Initial Standard Therapy in Multiple Myeloma) trial in multiple myeloma, in which a CR either after initial therapy or after relapse was equally associated with longer OS (Harousseau et al , 2010). …”
Section: Discussionmentioning
confidence: 96%
“…A subanalysis indicated that the quality of treatment response improved during continued VMP treatment, with 28% of CRs achieved during cycles 5--9, and the durability of the CR was similar regardless of when the CR was attained. 27 Furthermore, CR was associated with significantly longer time to progression, time to next therapy and treatmentfree interval versus partial response, but there was no difference in the OS. 27 Updated results from the VISTA study after a median of 36.7 months follow-up showed that VMP significantly reduced the risk of death by B35% compared with MP (HR ¼ 0.65, Po0.001); 3-year OS rates for the two regimens were 68.5% and 54.0%, respectively.…”
Section: Options Of Treatment As Induction Therapymentioning
confidence: 99%
“…27 Furthermore, CR was associated with significantly longer time to progression, time to next therapy and treatmentfree interval versus partial response, but there was no difference in the OS. 27 Updated results from the VISTA study after a median of 36.7 months follow-up showed that VMP significantly reduced the risk of death by B35% compared with MP (HR ¼ 0.65, Po0.001); 3-year OS rates for the two regimens were 68.5% and 54.0%, respectively. 19 The final OS analysis, conducted after a median follow-up of 60.1 months, demonstrated a persistent OS benefit of VMP over MP, with a 13.3-month increase in median OS (56.4 versus 43.1 months; HR ¼ 0.695; P ¼ 0.0004).…”
Section: Options Of Treatment As Induction Therapymentioning
confidence: 99%